The Implementation of Good Governance by the Local Government in the Management of Sasi in Morella Village, Leihitu Subdistrict, Central Maluku District - Pieter Soselisa; Rugayah Alhamid; Ivonny Rahanra (Universitas Sultan Ageng Tirtayasa, 2024)
This study aims to examine the implementation of 'sasi' (traditional ecological management) in the management of natural resources in current indigenous territories, particularly the government policy in Negeri Morella, Leihitu District, Central Maluku Regency, in organising the management of nutmeg plant resources. The enforcement of 'sasi' by the indigenous community for natural resource management represents a form of responsibility and manifestation of good governance in implementing natural resource management policies in Negeri Morella. The research approach used is qualitative, with a case study design. The research results indicate that the implementation of 'sasi' in indigenous territories in Maluku, especially in Central Maluku, has significantly reduced and, in some cases, is not implemented at all. Negeri Morella itself only enforces 'sasi pala' (nutmeg prohibition) with the main objective of supporting the economic resilience of the community households. The active involvement of the Negeri Morella Government in natural resource management through the enforcement of 'sasi' has had a positive impact on the community, ensuring the sustainability of the available resources for future generations.